The tight rope act: A multicenter regional experience of tourniquets in acute trauma resuscitation. Issue 5 (6th May 2022) - Tatebe, Leah Carey; Schlanser, Victoria; Hampton, David; Chang, Grace; Hanson, Isaac; Doherty, James; Issa, Nabil; Ghandour, Hani; Kingsley, Samuel; Stewart, Amy; Anstadt, Michael; Dennis, Andrew
Abstract : Of 216 tourniquets placed in Chicago, 64% had no arterial injury and 38% were not arterial occlusive. Focus should be placed on intuitive device development, universal standards of application, & ability to monitor quality measures. Abstract : BACKGROUND: As tourniquets have become more prevalent, device use has been questioned. This study sought to characterize the incidence, indication, and efficacy of tourniquet placement in acute trauma resuscitation. METHODS: Nine regional level 1 trauma centers prospectively enrolled for 12 months adult patients (18 years or older) who had a tourniquet placed. Age, sex, mechanism, tourniquet type, indication, applying personnel, location placed, level of occlusion, and degree of hemostasis were collected. Major vascular injury, imaging and operations performed, and outcomes were assessed. Analyses were performed with significance at p < 0.05. RESULTS: A total of 216 tourniquet applications were reported on 209 patients. There were significantly more male patients (183 [88%]) and penetrating injuries (186 [89%]) with gunshots being most common (127 [61%]). Commercial tourniquets were most often used (205 [95%]). Ninety-two percent were placed in the prehospital setting (by fire/paramedics, 56%; police, 33%; bystanders, 2%). The most common indications were pooling (47%) and pulsatile (32%) hemorrhage. Only 2% were for amputation. The most frequent location was high proximal extremity (70%). Four percent were placed over the wound, and 0.5% were distal to the wound. Only 61% of applications were arterial occlusive. Median application time was 30 minutes (interquartile range, 20–40 minutes). Imaging was performed in 54% of patients. Overall, 36% had a named arterial injury. Tourniquet application failed to achieve hemostasis in 22% of patients with a named vascular injury. There was no difference in hemostasis between those with and without vascular injury ( p = 0.12) or between who placed the tourniquet ( p = 0.07). Seventy patients (34%) required vascular operations. Thirty-four percent of patients were discharged home without admission. CONCLUSION: Discerning which injuries require tourniquets over pressure dressings remains elusive. Trained responders had high rates of superfluous and inadequate deployments. As tourniquets continue to be disseminated, emphasis should be placed on improving education, device development, and quality control. LEVEL OF EVIDENCE: Prognostic/Epidemiologic, Level III. Abstract :